Innovation et changement institutionnel : l'exemple des TPE - Anne Gustin (Nantes Université, 2009)
The present-day French school system is the result of successive steps to modernize school education; for a large part, this attempt has been induced at the institutional level and the schools have undertaken it. Therefore this article will consider the ability of the present-day school system to integrate innovation. This analysis will be conducted through the TPE (a Tutorial individual work) experiment, project which was gradually introduced by the Education Act 2000 concerning the "lycée" (i.e. General Certificate of Secondary Education). The purpose of this article is to give an overview of the checks that prevailed against the TPE and by extension an approach to the conditions for institutional change.